2021
DOI: 10.1620/tjem.255.19
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Effects of Artificial Fine Particulate Matter in Rats through Induction of Oxidative Stress and Inflammation

Abstract: Airborne fine particulate matter with an aerodynamic diameter equal to or smaller than 2.5 μm (abbreviated as PM 2.5 ) increases the risk of nasal lesions, but the underlying molecular mechanism has not been fully elucidated. In the atmosphere, the composition of PM 2.5 collected varies in physical and chemical properties, which affects its damage to human health. Thus, we constructed artificial PM 2.5 particles based on actual PM 2.5 and investigated the in vivo effects of artificial PM 2.5 exposure on the ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Guo et al demonstrated similar results in NLF collected from healthy rats exposed to PM2.5, which contained higher levels of IL-4, IL-13, and TGF-β1 compared to the control NLF [25]. Also, Hong et al showed that PM2.5 increased IL-1, IL-6, and TNF-α levels in the nasal mucosa of rats [36].…”
Section: Inflammatory Response In the Epitheliummentioning
confidence: 78%
See 2 more Smart Citations
“…Guo et al demonstrated similar results in NLF collected from healthy rats exposed to PM2.5, which contained higher levels of IL-4, IL-13, and TGF-β1 compared to the control NLF [25]. Also, Hong et al showed that PM2.5 increased IL-1, IL-6, and TNF-α levels in the nasal mucosa of rats [36].…”
Section: Inflammatory Response In the Epitheliummentioning
confidence: 78%
“…Interestingly, the levels of nuclear factor erythroid 2-related factor 2 (Nrf2), a key regulator of cellular oxidant resistance, were increased in the nucleus and decreased in the cytoplasm after PM2.5 treatment, suggesting that the nuclear translocation of Nrf2 was inhibited [35,37]. Analogous to these findings, Hong et al demonstrated that GSH-Px was downregulated in the nasal mucosa of rats exposed to PM2.5 and Gu et al demonstrated that PM2.5 exposure decreased GSH and increased MDA levels in human nasal epithelial cells [36,38].…”
Section: Disruption Of Epithelial Cell Metabolismmentioning
confidence: 91%
See 1 more Smart Citation
“…Consequently, the adaptive viral defence system is hampered, potentially leading to dysregulated immunopathological process in COVID-19 [ 41 , 42 ]. Exposure of PM2.5 has been associated with increased levels of reactive oxygen species (ROS) and the release of multiple proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), interleukin-1 (IL-1), and interleukin-6 (IL-6) [ 43 , 44 ]. Notably, oxidative stress plays a crucial role in COVID-19, with excessive ROS generation contributing to the onset of cytokine storms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that increased traffic-related PM 2.5 concentrations are associated with altered responses to inflammatory markers (51). Animal experiments have found that artificial PM 2.5 exposure can induce increased levels of interleukin (IL)-1, IL-6 and tumor necrosis factor α (TNFα) in rats, thereby increasing the risk of nasal lesions (52). Hypothyroidism is associated with disturbed cytokine concentrations, an abundance of reactive oxygen species (ROS), and altered signal transduction in most parts of the brain (53).…”
Section: Discussionmentioning
confidence: 99%